An ambiguous aspiration: school actors making sense of educational innovation policy - Edgar Quilabert (Taylor & Francis Group, 2024)
Educational innovation has received significant attention in contemporary policy debates. Many countries and regions have initiated comprehensive reforms to reshape teaching methods and link innovative practices with improved equity and performance outcomes. In Catalonia (Spain), a clear example of this phenomenon, recent policy developments have pressured schools and teachers to introduce innovative teaching practices to enhance the overall quality of the educational system. Yet, the conceptual framework of school innovation in this context is broad and ambiguous. Therefore, the Catalan case offers a rich context to explore how educational innovation policy is interpreted and enacted in schools. This study uses enactment and sensemaking theories, considering material, symbolic, and cognitive factors that explain variations in practices across schools. The study employs a qualitative approach to examine teachers' and principals' interpretations of the innovation policy and to analyse innovation practices. The findings show that the broad and ambiguous nature of the innovation policy mandate allows for wide interpretation, adaptation, and enactment, highly dependent on school actors' understandings of innovation and contextual factors. Additionally, schools often engage in innovation at a superficial level, with externally driven, fragmented, and standardized innovation practices being most frequent, although this varies across schools' socioeconomic levels.